Influence of liquid metal feeding on the flow and macrosegregation in DC casting. Issue 4 (3rd March 2020) - Coleman, J.; Krane, M. J. M.
ABSTRACT: The influence of liquid metal feeding on the flow and macrosegregation during direct chill (DC) casting of Al-4.5wt-%Cu billets is investigated. An analytical study for constricted inlets predicts that the inflow only reaches the bottom of the sump for narrow inlets, a result confirmed by steady-state axisymmetric simulations of equiaxed solidification. For wide inlets, and inlets using a combo bag, the inflow is swiftly entrained towards the chill and the final macrosegregation predictions are all similar. For narrow inlets without a combo bag, penetration of the thermal jet to the bottom of the sump locally delays solidification producing an inclination in the packed solid interface and the possible growth of columnar dendrites in this region.